Deteksi Dini Kesehatan Mental Emosional Siswa Sekolah Menengah Atas Sebagai Langkah Awal Menciptakan Generasi Unggul - Rosalia Putri; Srie Wayuni; Quranayati Quranayati; Pasyamei Rembune Kala; Mhd. Hidayattullah; Khaira Rizki (Lembaga Pengembangan Kinerja Dosen, 2025)
Survey on mental health in adolescents in Indonesia in 2022, 5.5% of adolescents aged 10-17 years experienced mental disorders. Mental health is a state of mental well-being that allows a person to cope with the pressures of life, study well, work well, and contribute to their community. Most of these psychological disorders are not recognized and do not receive proper treatment. The high proportion of depression in the young group, namely the population who at the time of the 2023 SKI was carried out were 15-24 years old or known as Gen Z or the strawberry generation, requires attention. Emotional mental disorders are conditions of individuals who experience emotional changes and in certain circumstances occur over a long period of time can develop and become pathological conditions. The aim is to identify emotional health disorders in adolescents in high school students as an initial step in creating a superior generation. This type of research is quantitative descriptive. The results of the study showed that 70% experienced symptoms of depression, 60% hyperactivity, 40% had peer problems, 64% showed abnormal behavior, 76% showed abnormal prosocial strength. The conclusion is that high school adolescents experience emotional mental health disorders that have an impact on educational achievement.